1987
DOI: 10.1523/jneurosci.07-04-00959.1987
|View full text |Cite
|
Sign up to set email alerts
|

Dissociated cingulate cortical neurons: morphology and muscarinic acetylcholine receptor binding properties

Abstract: Identifiable cortical neurons were obtained from area 29c of rat cingulate cortex using enzymatic and mechanical dissociation techniques. Dissociated neurons were either analyzed morphologically with the electron microscope or processed autoradiographically to evaluate the distribution of specific 3H-propylbenzilylcholine mustard (PrBCM) binding. Ultrastructurally, neurons appeared healthy and contained a full complement of cytoplasmic organelles. Membranes were intact and no presynaptic endings adhered to cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that neuroreceptor function, as well as various other aspects of cellular physiology, are well preserved (Sarthy, 1986). Ultrastructural studies have shown that papain-dissociated neurons have no presynaptic terminals adhering to them (Vogt et al, 1987;Lankford and Klein, unpublished data).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that neuroreceptor function, as well as various other aspects of cellular physiology, are well preserved (Sarthy, 1986). Ultrastructural studies have shown that papain-dissociated neurons have no presynaptic terminals adhering to them (Vogt et al, 1987;Lankford and Klein, unpublished data).…”
Section: Discussionmentioning
confidence: 98%
“…First, dissociated pyramidal neurons have specific binding of the nonselective antagonist propylbenzilylcholine mustard to their somata and 1°, 2°, and 3° basal and apical dendrites, i.e., the proximal integrative region including all proximal dendrites (Vogt et at., 1987). Second, ibotenic acid lesions of layers II -IV, which are composed primarily of small and fusiform pyramidal neurons , greatly reduce specific binding of pirenzepine in layers II-IV (i.e., the proximal compartment) as well as in all divisions of layer I (i.e., the distal dendritic compartment; Vogt and Burns, 1988).…”
Section: Cholinergic Projections: Organization and Role In Event Holdingmentioning
confidence: 99%
“…Second, ACh-evoked, slow depolarization in pyramidal neurons is PZ sensitive Prince, 1985, 1986). Third, high-resolution autoradiographic localization of PZ-sensitive sites to dendrites and somata has been made with dissociated cortical neurons (Vogt et al, 1987).…”
Section: Localization Of Dendritic M and M2 Sitesmentioning
confidence: 99%
“…Although cells can be dissociated and specific binding determined autoradiographically for identified types of adult neurons (Vogt et al, 1987) there are limitations to this approach. First, the only ligands appropriate for wet emulsion autoradiography are those that are irreversible, but propylbenzilylcholine mustard (PrBCM), which is irreversible, is not selective for a receptor subtype.…”
mentioning
confidence: 99%